The spirit of the Catholic aggiornamento: architecture, dialog and active participation - Miranda, B. P. (Actas del Congreso Internacional de Arquitectura Religiosa Contemporánea, 2015)
The Second Vatican Ecumenical Council aimed, in the words used by Pope John XXIII, the aggiornamento of the Catholic Church. The inseparable complementariness between the concept of resourcing and of openness to a new world led to a change of the paradigm of the church temple to the house for the living stones. It is in this context where it comes to light the opportunity to explore the contributions of two non-Christians architects: Aldo van Eyck, and Lina Bo Bardi. In their works and especially in their thoughts it is possible to recognize an elective affinity with the spirit of the Christian aggiornamento.